2018
DOI: 10.1371/journal.pgen.1007319
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of genetic circuitry and adaptive mechanisms enabling resistance to the azole antifungal drugs

Abstract: Invasive fungal infections caused by the pathogen Candida albicans have transitioned from a rare curiosity to a major cause of human mortality. This is in part due to the emergence of resistance to the limited number of antifungals available to treat fungal infections. Azoles function by targeting the biosynthesis of ergosterol, a key component of the fungal cell membrane. Loss-of-function mutations in the ergosterol biosynthetic gene ERG3 mitigate azole toxicity and enable resistance that depends upon fungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 79 publications
2
34
0
Order By: Relevance
“…We find that pep8 cells produce delayed or stunted hyphae and show attenuated macrophage escape (Figures 5, 6), confirming a role for this gene in filamentation as previously reported (Uhl et al, 2003) and suggesting a role in infection. This finding also confirms recent work, which is entirely independent from this study, that has shown that pep8 mutants demonstrate severe filamentation defects in a range of conditions (Azadmanesh et al, 2017) and these mutants abrogate azole resistance (Mount et al, 2018). Loss of function of Pep8 abrogates azole resistance by overwhelming the functional capacity of calcineurin.…”
Section: Discussionsupporting
confidence: 92%
“…We find that pep8 cells produce delayed or stunted hyphae and show attenuated macrophage escape (Figures 5, 6), confirming a role for this gene in filamentation as previously reported (Uhl et al, 2003) and suggesting a role in infection. This finding also confirms recent work, which is entirely independent from this study, that has shown that pep8 mutants demonstrate severe filamentation defects in a range of conditions (Azadmanesh et al, 2017) and these mutants abrogate azole resistance (Mount et al, 2018). Loss of function of Pep8 abrogates azole resistance by overwhelming the functional capacity of calcineurin.…”
Section: Discussionsupporting
confidence: 92%
“…To further address the mechanism of formation and to understand the impact of copy number on fitness, we used a set of isogenic isolates obtained from an agar plate instead of liquid cultures. These four single colony isolates (AMS3051, AMS3052, AMS3053, and AMS3054) were obtained from the same progenitor (AMS3050) after 120 hr growth on a single miconazole (20 μg/ml) agar plate ( Mount et al, 2018 ). Prior whole genome sequencing analysis of these colonies identified a shared CNV of Chr3L ( Mount et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…These four single colony isolates (AMS3051, AMS3052, AMS3053, and AMS3054) were obtained from the same progenitor (AMS3050) after 120 hr growth on a single miconazole (20 μg/ml) agar plate ( Mount et al, 2018 ). Prior whole genome sequencing analysis of these colonies identified a shared CNV of Chr3L ( Mount et al, 2018 ). To test the hypothesis that these single colonies represented different outcomes from the same recombination event, due to the short exposure to miconazole and similarity in karyotypes, we first performed read depth analysis to characterize the CNV breakpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Growth in fluconazole is expected to exert selection pressure for some aneuploids more than others; specific genes within an aneuploid chromosome that are responsible for increased drug resistance (26) and drug tolerance (27) also have been identified. In many other cases, more than one gene may contribute to the phenotype (22,27,48,68,69). While we assume that changes in DNA content of a given isolate are largely due to chromosomal aneuploidy, it is important to note that increased levels of mitochondrial and/or ribosomal DNA can also contribute to differences in DNA content level detected by flow cytometry, as was recently shown to occur in different deletion mutants within the "isogenic" collection of Saccharomyces cerevisiae deletion mutants (70).…”
Section: Discussionmentioning
confidence: 97%